Development of LKPD (Student Worksheets) Based on Learning Cycle 5E Assisted by PhET Simulation to Improve Scientific Reasoning Skills for Junior High School Students - Mahbubah, Isna Nikmatul; Nuha, Ulin; Ahmad, Nur (FKIP - Universitas Riau, 2024)
One of the factors in achieving student learning outcomes is scientific reasoning abilities (Scientific Reasoning) which will help students understand the main concepts of science. However, the PISA study categorized Indonesian students' scientific reasoning abilities as low, ranking 70th out of 78 countries in science and mathematics. This research aims to develop LKPD based on Learning Cycle 5E assisted by PhET Simulation that is valid, practical and effective. The type of research developed is Research and Development (R&D) using the ADDIE model. The research subjects were students of class IX semester 1 at SMPN 1 Jenggawah. The research data was analyzed based on several criteria. The results of the LKPD development obtained validity test results with a score of 91% (very valid). The practicality test results obtained an average score of 92.5% (practical). The results of the effectiveness test obtained an average N-Gain of 0.67 (medium). Based on the research findings, LKPD based on Learning Cycle 5E assisted by PhET Simulation can provide innovation in learning resources as an alternative to improve the scientific reasoning abilities of junior high school students.